Analisis Hukum Perbankan Konversi Bank Konvensional Menjadi Bank Syariah - nurhadi nurhadi (Indonesia, 2021)
Conventional Banks can change business activities into Sharia Banks, but not vice versa. Changes in business activities for commercial banks and rural banks must obtain permits and meet requirements. After permission is obtained, it must clearly state the word "Sharia" on the writing of the name, and the iB logo on the forms, documents, products, offices, and networks of Sharia Bank offices. The hierarchy as a legal basis is: 1). Law Number 7 of 1992 concerning Banking as amended by Act Number 10 of 1998 concerning Amendment to Law Number 7 of 1992 concerning Banking; 2). Law Number 21 of 2008 concerning Sharia Banking; 3). Financial Services Authority Regulation Number 64 / POJK.03 / 2016 Year 2016 concerning Changes in Conventional Bank Business Activities to Sharia Banks; 4). Financial Services Authority Circular Letter Number 2 / SEOJK.03 / 2017 Year 2017 concerning Changes in Business Activities of Conventional Commercial Banks to Islamic Commercial Banks. The mechanism described above must be carried out by conventional banks that want to change business activities into Islamic banks. The conversion effort must be supported always to increase the growth of Indonesian sharia banking. The amount of public interest in the existence of Islamic banking and foreign investors who want to invest in Indonesia must be accommodated with the growth of Islamic banking through an increase in the sharia banking office network in each region in Indonesia.